Viral Metagenomics of chickens with respiratory infection using MG-RAST - Sajnani, Manisha R.; Sudarsanam, D.; Jakhesara, Subhash J.; Solosanc, Siddhardha; Joshi , Chaitanya G.; Bhatt, Vaibhav D. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Respiratory tract infections in poultry flocks lead to increased rate of mortality and thereby increase economic burden to the poultry industry. The aim of the study was to identify variety of known and unknown microbial organisms participating in the respiratory tract infections in poultry. Infected samples from 8 different poultry farms located in the Anand district of Gujarat, India were collected. Using Next Generation Sequencing (NGS) platform Ion Torrent PGM, approximately 1.1 giga-bases of sequences by metagenomics pipeline were obtained. To understand the community of bacterial as well as viral sequences involved in the infection, MG-RAST, an automated online based approach was used. The taxonomical classfication resulted in sequences with 78.91% of bacteria, 9.35% of eukaryota, 8.17% of viruses, 0.10% of archaea, 0.02% of unclassified sequences, 0.45% of other sequences and 2.99% were unannotated. While functional classification of sequences resulted in 22.15% of predicted proteins with known functions, 77.74% of predicted proteins with unknown function, and very negligible 0.01% of ribosomal RNA genes. The most abundant virus families observed were Podoviridae, Myoviridae and Siphoviridae belonging to the Caudovirales order. This study is the first approach for annotating metagenomics of poultry having respiratory infection using MG-RAST approach.